2015
DOI: 10.1002/ajh.24120
|View full text |Cite
|
Sign up to set email alerts
|

Age and dPCR can predict relapse in CML patients who discontinued imatinib: The ISAV study

Abstract: Imatinib is effective for the treatment of chronic myeloid leukemia (CML). However even undetectable BCR-ABL1 by Q-RT-PCR does not equate to eradication of the disease. Digital-PCR (dPCR), able to detect 1 BCR-ABL1 positive cell out of 10 7 , has been recently developed. The ISAV study is a multicentre trial aimed at validating dPCR to predict relapses after imatinib discontinuation in CML patients with undetectable Q-RT-PCR. CML patients under imatinib therapy since more than 2 years and with undetectable PCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
190
2
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 191 publications
(214 citation statements)
references
References 28 publications
18
190
2
4
Order By: Relevance
“…This analysis was based on additional clinical observations: first, we observed an interesting phenomenon in some patients who developed musculoskeletal pain with or without pruritus after discontinuation of IM, implying a possible link to autoimmunity; 11 and second, detectable minimal residual leukemia by the more sensitive approach of dPCR may have a significant positive predictive value for molecular relapse. 9 In this study, we observed that most IM-related adverse events such as nausea, indigestion, peripheral edema, and skin whitening and fragility were rapidly resolved, whereas musculoskeletal pain and pruritus were newly developed or worsened in some patients after IM discontinuation. These observations are similar to the findings of the S.-E. Lee et al 720 haematologica | 2016; 101(6) …”
Section: Discussionmentioning
confidence: 75%
See 4 more Smart Citations
“…This analysis was based on additional clinical observations: first, we observed an interesting phenomenon in some patients who developed musculoskeletal pain with or without pruritus after discontinuation of IM, implying a possible link to autoimmunity; 11 and second, detectable minimal residual leukemia by the more sensitive approach of dPCR may have a significant positive predictive value for molecular relapse. 9 In this study, we observed that most IM-related adverse events such as nausea, indigestion, peripheral edema, and skin whitening and fragility were rapidly resolved, whereas musculoskeletal pain and pruritus were newly developed or worsened in some patients after IM discontinuation. These observations are similar to the findings of the S.-E. Lee et al 720 haematologica | 2016; 101(6) …”
Section: Discussionmentioning
confidence: 75%
“…Increased IM therapy duration was reported to be strongly associated with a higher probability of sustained UMRD in previous studies. 1,3,6,7 Sokal risk score, 1,4,6 sex, 1 prior interferon treatment, 4,7 UMRD duration before IM discontinuation, 3,7 time to UMRD, 6 age, 9 and dPCR 9 were also reported as potential predictive factors, albeit with conflicting data. To identify additional predictors and to validate predictors explored in our previous study, 3 we performed further analysis with more patients who had at least 12 months of follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations